Efficiency of international humanitarian law in protection of journalists during armed conflicts - Vecvagare, Tīna (Riga Graduate School of Law, 2018)
The thesis aims to determine what are the factors hindering efficiency of international humanitarian legal frameworks in place for the protection of journalists which have a vital role in a democracy during armed conflicts. Research examines the distinctions which determine the protection granted by the IHL to journalists during armed conflicts and deals with the efficiency of legal frameworks in place for the protection of journalists during armed conflicts.